The relationship between job stress and patient safety culture among nurses: a systematic review - Loai M. Zabin; Rasha S. Abu Zaitoun; Esa M. Sweity; Lila de Tantillo (BMC Nursing, 2023)
Abstract Background Work stress is one of the leading causes of physical and mental problems among nurses and can affect patient safety. Nurses experiencing stress are more prone to make errors, which has consequences for the safety culture. This study aimed to describe the findings of studies that examined the relationship between job stress and patient safety culture among nurses. Methods A systematic review of published English-language articles from 2017 to 2021 was obtained through an electronic search of three large online databases (i.e., CINAHL through EBSCOhost, Medline through PubMed, and Embase). We used the Statement of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to guide the undertaking of this review. In addition, data extraction and quality assessment were performed for the final seven quantitative articles. Results This review showed a significant relationship between job-related stress in its different factors, patient safety culture, and patient safety. Three studies of the seven reviewed articles examined the relationship. The rest of the studies examined the relationship indirectly, discussing factors that impacted job stress and how they affected patient safety culture. However, differences in working conditions and study characteristics affected the results of these studies and the significance of this relationship. Conclusions This review suggests that nursing managers and administrators should consider actions to minimize nursing job stress to the minimum levels and improve their work environment to provide the best possible patient care. Future studies are needed to develop interventions to reduce workplace stress and improve nurses' safety. Furthermore, nurses’ managers and educators should train nurses on resilience and how to work in trauma-informed care.